Exo / 1. - Lee, Fonda (Scholastic Press, 2017)
For a century now, Earth has been a peaceful colony of an alien race, and Donovan Reyes is a loyal member of the security forces, while his father is the Prime Liaison--but when a routine search and seizure goes bad Donovan finds himself a captive of the human revolutionary group, Sapience, terrorists who seem to prefer war to alien rule, and killing Donovan just might be the incident they are looking for.